Role of Dihydrolipoamide Dehydrogenase in Regulation of Raffinose Transport in Streptococcus pneumoniae - Tyx, Robert E. (American Society for Microbiology, 2011)
Streptococcus pneumoniae strains lacking the enzyme dihydrolipoamide dehydrogenase (DLDH) show markedly reduced ability to grow on raffinose and stachyose as sole carbon sources. Import of these sugars occurs through the previously characterized raffinose ATP-binding cassette (ABC) transport system, encoded by the raf operon, that lacks the necessary ATP-binding protein. In this study, we identified the raffinose ATP-binding protein RafK and showed that it was directly involved in raffinose and stachyose import. RafK carries a C-terminal regulatory domain present in a subset of ATP-binding proteins that has been involved in both direct regulation of transporter activity (inducer exclusion) and transcription of transporter genes. Pneumococci lacking RafK showed a 50- to 80-fold reduction in expression of the raf operon genes aga (alpha-galactosidase) and rafEFG (raffinose substrate binding and permease genes), and both glucose and sucrose inhibited raffinose uptake through inducer exclusion. Like RafK, the presence of DLDH also activated the expression of raf operon genes, as DLDH-negative pneumococci showed a significantly decreased expression of aga and rafEFG, but DLDH did not regulate rafK or the putative regulatory genes rafR and rafS. DLDH also bound directly to RafK both in vitro and in vivo, indicating the possibility that DLDH regulates raffinose transport by a direct interaction with the regulatory domain of the transporter. Finally, although not as attenuated as DLDH-negative bacteria, pneumococci lacking RafK were significantly outcompeted by wild-type bacteria in colonization experiments of murine lung and nasopharynx, indicating a role for raffinose and stachyose transport in vivo.